2010
DOI: 10.1200/jco.2009.27.9158
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Plus Dexamethasone Is Superior to Vincristine Plus Doxorubicin Plus Dexamethasone As Induction Treatment Prior to Autologous Stem-Cell Transplantation in Newly Diagnosed Multiple Myeloma: Results of the IFM 2005-01 Phase III Trial

Abstract: Bortezomib plus dexamethasone significantly improved postinduction and post-transplantation CR/nCR and at least VGPR rates compared with VAD and resulted in a trend for longer PFS. Bortezomib plus dexamethasone should therefore be considered a standard of care in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
366
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(388 citation statements)
references
References 42 publications
20
366
0
2
Order By: Relevance
“…Harousseau et al compared bortezomib plus dexamethasone (VD) versus vincristine, Adriamycin, dexamethasone (VAD) as pretransplant induction therapy [56]. Post-induction very good partial response (VGPR) was superior with VD compared with VAD, 38% versus 15%, respectively.…”
Section: Risk-adapted Therapymentioning
confidence: 99%
“…Harousseau et al compared bortezomib plus dexamethasone (VD) versus vincristine, Adriamycin, dexamethasone (VAD) as pretransplant induction therapy [56]. Post-induction very good partial response (VGPR) was superior with VD compared with VAD, 38% versus 15%, respectively.…”
Section: Risk-adapted Therapymentioning
confidence: 99%
“…[1][2][3] Over the last decade, novel drugs, particularly immunomodulatory (IMID) agents and proteasome inhibitors, have been incorporated into the pre-transplantation induction therapy and have improved the rate of complete response both before and after autologous transplantation. [4][5][6] The use of the IMID lenalidomide in the induction regimen was early identified as a risk factor for poor AHSC mobilization. [7][8][9][10] This negative effect, noticed particularly with growth factor mobilization, is at least partially overcome with the use of chemotherapy mobilization, [11][12][13] although this strategy carries higher cost and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit conferred by thalidomide combinations in induction was confirmed by the Myeloma IX and Total Therapy 2 trials (Morgan et al, 2012;Barlogie et al, 2006b). The IFM 2005-01 trial demonstrated that bortezomib and dexamethasone was also superior to VAD, increasing the pre-ASCT response rate to 79% from 63%, (Harousseau et al, 2010), and a similar improvement with bortezomib-based induction was observed in the HOVON65/GMMGHD4 trial (Sonneveld et al, 2012). Cavo et al tested the addition of bortezomib to thalidomide plus dexamethasone, and this combination of both IMiD and proteasome inhibitor significantly improved both pre-ASCT ORR (93% vs. 79%) and progression-free survival (PFS) (Cavo et al, 2010).…”
Section: Novel Agent Inductionmentioning
confidence: 75%